1987
DOI: 10.1016/0035-9203(87)90020-4
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and natural resistance of Trypanosoma cruzi strains to drugs used clinically in Chagas disease

Abstract: The susceptibility and natural resistance to two nitroheterocyclic derivatives used clinically in Chagas disease (nifurtimox and benznidazole) were investigated in 47 Trypanosoma cruzi strains isolated from human patients, domestic vectors and sylvatic reservoirs or vectors. A large gradient of drug efficacy from 0% to 100% was detected. Drug susceptibility apparently related to geographical distribution of some T. cruzi strains was also observed. Drug resistance was identified among T. cruzi populations isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
378
2
27

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(420 citation statements)
references
References 6 publications
13
378
2
27
Order By: Relevance
“…Major parasite surface components, such as TS/gp85 glycoproteins, mucins, and surface proteases GP63, were found in extracellular vesicles (EVs) shed by infective trypomastigote forms of the parasite [9,10]. Trypanosoma cruzi EVs modulate infectivity, since pre-treatment of BALB/c mice followed by parasite challenge, exacerbated parasite load, heart inflammation, and mortality [11]. Recently, protein and α-galactosyl variations in EVs from different T. cruzi strains (Y, Colombiana, CL-14, and YuYu) suggested that intraspecies polymorphisms in those structures could correlate with their ability to induce proinflammatory cytokines [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major parasite surface components, such as TS/gp85 glycoproteins, mucins, and surface proteases GP63, were found in extracellular vesicles (EVs) shed by infective trypomastigote forms of the parasite [9,10]. Trypanosoma cruzi EVs modulate infectivity, since pre-treatment of BALB/c mice followed by parasite challenge, exacerbated parasite load, heart inflammation, and mortality [11]. Recently, protein and α-galactosyl variations in EVs from different T. cruzi strains (Y, Colombiana, CL-14, and YuYu) suggested that intraspecies polymorphisms in those structures could correlate with their ability to induce proinflammatory cytokines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Those strains displayed significant biological differences regarding infectivity [19], drug resistance [11], and immunomodulation [12]. Purified EVs and soluble fractions from Y and YuYu strains were characterized by liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la efectividad del tratamiento puede verse afectada por algunos factores, tales como: 1) fase de la enfermedad, con 70 % de los pacientes considerados recuperados en la fase aguda y sólo 20 % en la fase crónica; 2) estado fisiológico, inmunológico y edad de los pacientes; 3) efectos colaterales de los medicamentos; 4) falta de cumplimiento del tratamiento, y 5) la expresión de resistencia a estos compuestos por parte del parásito (5)(6)(7)(8).…”
Section: Sensibilidad Al Benzonidazol De Trypanosoma Cruziunclassified
“…Algunos trabajos reportan que 27 % de las cepas de T. cruzi aisladas de diferentes orígenes biológicos y geográficos, poseen resistencia natural al benzonidazol y al nifurtimox, con porcentajes de curación menores de 50 % en ratones, a pesar de nunca haber estado en contacto con estos medicamentos (8). Además, se reportó que es posible inducir resistencia en este parásito, tanto in vitro como in vivo, por presiones continuas con estos medicamentos (12)(13)(14)(15), lo cual genera poblaciones resistentes a concentraciones de benzonidazol de hasta 220 μM (15), y se han propuesto algunos genes involucrados en el surgimiento del fenotipo de resistencia a este medicamento (12,13,(16)(17)(18)(19)(20)(21).…”
Section: Sensibilidad Al Benzonidazol De Trypanosoma Cruziunclassified
“…Nifurtimox and benznidazole, discovered over 40 years ago and still the only available drugs for the specific treatment of Chagas' disease, are limited by toxicity and low efficacy in the established chronic form of the disease [7]. These major drawbacks, along with upcoming reports of resistant T. cruzi [8] and the spread of the disease to nonendemic countries [2], spurred renewed drug research and development (R&D) for Chagas' disease. The triazoles posaconazole and E1224 were the only candidates to pass the preclinical phase and enter clinical proof-of-concept trials.…”
mentioning
confidence: 99%